The complex methylome of the human gastric pathogen Helicobacter pylori. Issue 4 (2nd December 2013) - Krebes, Juliane; Morgan, Richard D.; Bunk, Boyke; Spröer, Cathrin; Luong, Khai; Parusel, Raphael; Anton, Brian P.; König, Christoph; Josenhans, Christine; Overmann, Jörg; Roberts, Richard J.; Korlach, Jonas; et al.
Abstract: The genome of Helicobacter pylori is remarkable for its large number of restriction-modification (R-M) systems, and strain-specific diversity in R-M systems has been suggested to limit natural transformation, the major driving force of genetic diversification in H. pylori . We have determined the comprehensive methylomes of two H. pylori strains at single base resolution, using Single Molecule Real-Time (SMRT®) sequencing. For strains 26695 and J99-R3, 17 and 22 methylated sequence motifs were identified, respectively. For most motifs, almost all sites occurring in the genome were detected as methylated. Twelve novel methylation patterns corresponding to nine recognition sequences were detected (26695, 3; J99-R3, 6). Functional inactivation, correction of frameshifts as well as cloning and expression of candidate methyltransferases (MTases) permitted not only the functional characterization of multiple, yet undescribed, MTases, but also revealed novel features of both Type I and Type II R-M systems, including frameshift-mediated changes of sequence specificity and the interaction of one MTase with two alternative specificity subunits resulting in different methylation patterns. The methylomes of these well-characterized H. pylori strains will provide a valuable resource for future studies investigating the role of H. pylori R-M systems in limiting transformation as well as in gene regulation and host interaction.